Effect of World Bank Loan Withdrawal on the Performance of Agricultural Extension in Nigeria (Nordic Journal of African Studies, 2004)
This paper examined the effect of World Bank loan withdrawal on the performance of extension services in Nigeria. This was because agricultural extension activities were tripartitely funded by World Bank, State and Federal governments in Nigeria. The final withdrawal would then have serious implications for the performance of the extension organizations. Data were obtained from secondary sources and analyzed using t-test statistics. The result indicates that there were sharp decline in the performance of extension activities after the loan withdrawal and thus the question of sustainability of the Agricultural Development Programme.